Pengaruh Social Media Marketing Activities dan Lifestyle terhadap Keputusan Pembelian Generasi Z di Coffee shop Garut - Maitri Putri Noer Haifa; Hilman Rismanto; Gita Garliani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of Social Media Marketing Activities (SMMA) and lifestyle on Generation Z purchasing decisions at coffee shops in Garut. A quantitative research approach was employed using a survey method involving 180 Generation Z respondents who had previously made purchases at coffee shops and actively used social media. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that lifestyle has a positive and significant effect on purchasing decisions, with a path coefficient of 0.611 (t = 9.791; p < 0.001), while Social Media Marketing Activities also demonstrate a positive and significant effect, with a coefficient of 0.291 (t = 4.538; p < 0.001). The R² value of 0.701 indicates that both variables explain 70.1% of the variance in purchasing decisions. These results suggest that lifestyle exerts a more dominant influence than social media marketing activities in shaping Generation Z purchasing decisions. This study provides practical implications for coffee shop businesses to integrate digital marketing strategies with experience and value creation aligned with young consumers’ lifestyles. Theoretically, this research contributes to the enrichment of consumer behavior literature, particularly within non-metropolitan contexts.